Mengimplementasikan Prinsip Pengembalaan Menurut 1 Petrus 5:1-5 - Ceria Ceria; Robert Octavianus; Sudiadi Siregar; Almart Yosfri Simamora (DIEGESIS: Jurnal Teologi Kharismatika, 2021)
Every pastor must have principles in carrying out his ministry as the main guide in acting and thinking in carrying out his ministry duties. The pattern of life and character of a pastor in carrying out pastoral ministry greatly affects the life of the congregation, therefore it is necessary to understand how the principles of pastoral care and also the pattern in their application in the ministry itself The use of 1 Peter 5-1:5 is not without reason, this is because there are pastors who are not fully aware of the duties and responsibilities associated with the position as pastor of the congregation, and this is what encourages the author to compile and explore what the Bible says about the principles of shepherding in 1 Peter 5:1-5 and how these principles can be applied in service today. Research method, the author uses a qualitative research method approach to descriptive analysis, with an exposition approach to the text of 1 Peter 5:1-5, namely: first, the shepherd has the responsibility to feed his sheep, serve not because forced and looking for personal gain, and placing oneself as a servant, namely serving the congregation and having a willingness to serve unconditionally and being willing to sacrifice in carrying out services for the benefit of the congregation.AbstrakSetiap gembala harus memiliki prinsip pelayanan sebagai pedoman bertindak dan berpikir da-lam melakukan tugas pelayanannya. Pola hidup dan karakter seorang gembala dalam menjalan-kan pelayanan Pastoral mempengaruhi kehidupan jemaat. Oleh sebab itu sangat diperlukan pe-mahaman tentang prinsip-prinsip pengembalaan. Penggunaan 1 Petrus 5-1:5 bukanlah tanpa ala-san, penulis untuk menyusun dan menggali apa kata Alkitab tentang bagaimana prinsip-prinsip penggembalaan dalam surat 1 Petrus 5:1-5, dan bagaimana prinsip tersebut dapat diterapkan da-lam pelayanan saat ini. Metode penelitian, penulis menggunakan pendekatan metode penelitian kualitatif analisis deskriptif, dengan pendekatan eksposisi pada teks 1 Petrus 5:1-5. Yakni, gem-bala menyadari tanggung jawabnya dalam memberi makan dombanya serta melayani bukan karna terpaksa dan mau menempatkan diri sebagai seorang hamba yaitu melayani jemaat serta memiliki kerelaan hati untuk mengabdi tanpa pamrih dan rela berkorban dalam melakukan pelayanan-pelayanan demi kepentingan jemaatnya.